Adaptive life cycle costing (LCC) modeling and applying to Italy ceramic tile manufacturing sector: Its implication of open innovation - María Sonia Medina-Salgado; Fernando E. García-Mui\~na; Marco Cucchi; Davide Settembre-Blundo (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Converging business, sustainability, and technology is a challenge that manufacturing firms face to create value and be competitive. Energy- and raw material-intensive manufacturing industries are particularly aware of environmental issues and circular economy practices due to the large amounts of resources they use. However, manufacturing companies must also be mindful of economic sustainability in order to make their business profitable. For this, appropriate economic evaluation tools are needed, one of which is life cycle costing (LCC). LCC, when applied to the manufacturing context, is often considered as a simple extension of the life cycle assessment (LCA). This is the main limitation of LCC, as it only contributes to determining the economic value of environmental damage. This research aims to overcome this limitation, analyzing the Italian ceramic tile manufacturing sector as a case study in order to conceptually develop, through the abductive methodology, a calculation framework that extends the potential of LCC by including circularity parameters. Subsequently, the conceptual framework is empirically validated using sectoral industrial costs by configuring two scenarios (with and without circularity practices) and building a benchmark for individual firms in this industry. Finally, the research includes some considerations on the positive implications and potential of life cycle costing in an open innovation context.
Keywords: 650; ceramic tiles; circular economy; economic sustainability; industrial management; life cycle costing; manufacturing; open innovation